Platelet Effects of Anti-diabetic Therapies: New Perspectives in the Management of Patients with Diabetes and Cardiovascular Disease - Nusca, Annunziata; Tuccinardi, Dario; Pieralice, Silvia; Giannone, Sara; Carpenito, Myriam; Monte, Lavinia; Watanabe, Mikiko; Cavallari, Ilaria; Maddaloni, Ernesto; Ussia, Gian Paolo; Manfrini, Silvia; Grigioni, Francesco (Frontiers in Pharmacology, 2021)
In type 2 diabetes, anti-thrombotic management is challenging, and current anti-platelet agents have demonstrated reduced efficacy. Old and new anti-diabetic drugs exhibited –besides lowering blood glucose levels- direct and indirect effects on platelet function and on thrombotic milieu, eventually conditioning cardiovascular outcomes. The present review summarizes existing evidence on the effects of glucose-lowering agents on platelet properties, addressing pre-clinical and clinical research, as well as drug-drug interactions with anti-platelet agents. We aimed at expanding clinicians’ understanding by highlighting new opportunities for an optimal management of patients with diabetes and cardiovascular disease. We suggest how an improvement of the thrombotic risk in this large population of patients may be achieved by a careful and tailored combination of anti-diabetic and anti-platelet therapies.